(untitled) - Nancy Wiegersma (New York, 1988)
This book presents a clear picture of traditional Vietnam and then shows the dynamics of change during French colonialism, the American intervention and the present socialist period. It also offers answers to questions about "heart and minds" unanswered by the voluminous journalism of the Vietnam War period and promotes a deep understanding of revolutionary forces in Vietnamese society and how the United States intervention influenced these forces
Keywords: farm tenancy - vietnam - history,peasantry - vietnam - history,vietnam - rural conditions